2012
DOI: 10.1016/j.dental.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite containing CaF2 nanoparticles: Thermal cycling, wear and long-term water-aging

Abstract: Objectives Fluoride (F) releasing dental restoratives are promising to promote remineralization and combat caries. The objectives of this study were to develop nanocomposite containing calcium fluoride nanoparticles (nCaF2), and to investigate the long-term mechanical durability including wear, thermal-cycling and long-term water-aging behavior. Methods Two types of fillers were used: nCaF2 with a diameter of 53 nm, and glass particles of 1.4 μm. Four composites were fabricated with fillers of: (1) 0% nCaF2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 48 publications
(82 reference statements)
0
52
0
Order By: Relevance
“…For that reason, thermal cycling is usually performed between 5 and 55 • C with cycle times of 1 min [19][20][21]. The suggested duration of thermal cycling differs from 3000 to 100,000 cycles [22][23][24][25][26]. It is proposed that 10,000 cycles might represent 1 year of service [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, thermal cycling is usually performed between 5 and 55 • C with cycle times of 1 min [19][20][21]. The suggested duration of thermal cycling differs from 3000 to 100,000 cycles [22][23][24][25][26]. It is proposed that 10,000 cycles might represent 1 year of service [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, new silorane monomers 1) and modified urethane (meth) acrylates such as TCD-urethane 2) that decrease polymerization shrinkage have been developed; filler refinement 3,4) using nanotechnology has been widely applied not only to reduce particle size, but also to increase filler volume to enhance polishing and wear resistance. Also special fillers that release fluoride have been introduced 5) . In addition, bulk fill composite restorations have been made possible with the development of new photoinitiators 6) (such as Tetric-N-Ceram Bulk Fill, Ivoclar Vivadent), and flowable composite resins that can be directly inserted through a cannula to easily line the base of cavities with complicated shapes have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the fluoride release from a conventional glass ionomer cement and from a fluoride nanoparticle, Neelakantan et al 25 observed a higher release for the conventional ionomer on the first three days, but a maximum release. Since fluoridereleasing dental restoratives are promising to promote remineralisation and to combat caries, Weir et al 26 developed nanocomposites containing calcium fluoride nanoparticles (nCaF 2 ) and investigated their long-term mechanical durability including wear, thermal-cycling and long-term water-aging behavior. Combining nCaF 2 with glass particles yielded nanocomposites with long-term mechanical properties and with little fluoride release, indicating that the nCaF 2 nanocomposites are promising for load-bearing and caries-inhibiting restorations.…”
Section: Nanotechnology and Dental Applicationsmentioning
confidence: 99%